Portfolio Analysis on Distance Education Faculty Members - Asaari, Muhammad Hasmi Abu Hassan (AESS Publications, 2019)
This paper examines the faculty members of distance education on their performance in relation to the BCG portfolio analysis. The faculty members were examined on their number of publications during the periods of 2010 to 2018; namely a lady boss (2010-2013) vs. a male boss (2014-2018). The process of data mining was done by using Google Scholar and faculty members’ website hosted by the school. Data analyses were done through the interpretation of data by using the matrix of the number of publications and number of years. The data was plotted on the BCG portfolio analysis in the quadrants, namely cash cow, star, question mark, dog, and in between quadrants. The plotting of the faculty members on the quadrants give a crystal clear to the head of the department on the historical evidence of faculty members performance in the past 9 years. Moreover, the information presented would be useful for the head of the department in determining the directions and directives toward achieving the school's key performance index by the end of 2019